A violência por parceiro íntimo (VPI) em casais homoafetivos masculinos: visibilizando o fenômeno - Alexandro Martins Moreira (2017)
Intimate Partner Violence (IPV) is a term that covers multiple faces in the phenomenon of violence comprised in intimate relationships. It includes both heterosexual and homosexual relationships and widens the gaze to the various ways of being intimately related, with no relationship or gender constraints. It is understood, especially with regard to homoaffective relations, that there is still an invisibility of the phenomenon and in this sense, this research had as its central objective to study the perception that gay men have about Intimate Partner Violence, seeking to produce greater visibility on the same. In addition, the following specific objectives: Identify the perception of gay men about violence and IPV; Identify situations of violence and IPV experienced; Describe ways to deal with violence and IPV; To identify triggering factors for the occurrence of IPV in homoaffective relationships; Identify the knowledge of the structures of care for situations of IPV for gay men. This is a qualitative and exploratory research of the case study type, which used documentary research and semistructured interviews as instruments of data collection. In the documentary research, academic papers on the subject, laws, reports and manuals were researched, in order to systematize the concept of IPV and its typification; Risk and protection factors that may be linked to the phenomenon; Possible criminal justice processes; And the concept of gender, gender identity, sexual orientation and homosexuality. The interviews were carried out in the city of Belo Horizonte, with key informants as gay men members of the Center for Fight for Free Sexual Orientation (CELLOS), which is a militant civil society entity that fights for the rights and promotion of citizenship of the lesbian, Gay, bisexual, transvestite and transgender people - LGBT, as well as against LGBTophobia and all forms of prejudice. The choice of these key informants was by criterion of convenience and a total of 6 were interviewed. The data were analyzed through Bardin's Content Analysis, resulting in the following categories: characteristics of the respondents; Relationship with sexuality; Family relationship; Understanding of violence; Violence, ways of dealing with violence; Understanding of VPI; Experience of IPV; Ways to deal with IPV; Factors that contribute to IPV, knowledge of LGBT community service structures in situations of violence and difficulties in dealing with IPV. The results indicated that the interviewees had a broader understanding of violence and IPV. In addition, many reported episodes of violence that had already occurred and / or IPV, and all of them reported knowing people who had already had IPV. The factors that could influence this type of violence were mostly based on the masculinity standards, but also on the specific singularities of this group, highlighting prejudice, discrimination, social invisibility and nonguarantee of rights. Regarding the knowledge of the structures of service to the LGBT community in situations of violence, many reported knowing, even superficially, but there was consensus in the assessment that gays do not know them and would not seek them out. With regard to the difficulties encountered in dealing with VPI, it was highlighted the lack of preparation of government structures to meet this demand as well as the great social stigma that plagues the gay community. Further studies on the phenomenon and incorporation of the theme into the public agenda are needed.